Characterization of soft soil using multi-channel analysis of surface waves (MASW) and electrical resistivity method (ERM) - Basri, Kasbi (2017)
This thesis demonstrates the research on the soft soil characteristics using geophysical methods. The need on non-intrusive, time efficient, economic and larger volume of investigation had increased the demand of using geophysical methods for geotechnical investigation. The research concentrates on the determination of soft soil shear-wave velocity (Vs) profile using the multi-channel analysis of surface waves (MASW) and the soil stratigraphy using Electrical Resistivity Method (ERM). The soft soil Vs and stratigraphy were determined and correlated with the peat sampler and borehole data to obtain more accurate data. The research was conducted at Parit Nipah and RECESS UTHM. The Vs obtained for peat and soft clay at Parit Nipah was in the range of 29.7 to 34.9 m/s and 36.8 to 76.9 m/s respectively. While, the soft clay Vs obtained at RECESS was in the range of 64.4 to 124.0 m/s. The lower Vs obtained on peat compared to soft clay was due to the heterogeneity of peat. The soil strata obtained by ERM had good agreement with the peat sampler and borehole data. The resistivity value of peat and soft clay obtained at Parit Nipah was in the range of 47.2 to 127.7 ohm.m and 9.4 to 25.8 ohm.m correspondingly. While, at RECESS soft clay, the resistivity value was in the range of 1.0 to 4.6 ohm.m. The lower resistivity value of soft clay was governed by the amount of clay fraction which was related to cation exchange capacity (CEC). As higher CEC results in higher conductivity. The relationship obtained between the 1-D Vs and 1-D resistivity value shows that consistent value of peat Vs was followed by the slight decrease in peat resistivity value. While, drastic increase in soft clay Vs results in a significant decrease in soft clay resistivity value. This concluded that stiffness does not produce significant effect on the soil resistivity. Overall, MASW and ERM produced high quality data for subsurface investigation in larger volume with timely efficient manner and more economic.